Changes in the Position of the Junctional Vertebrae After Posterior Spinal Fusion in Adolescent Idiopathic Scoliosis: Implication in Risk Assessment of Proximal Junctional Kyphosis Development. Issue 2 (February 2020) - Homans, Jelle F.; Kruyt, Moyo C.; Schlösser, Tom P.C.; Colo, Dino; Rogers, Kenneth; Shah, Suken A.; Flynn, John M.; Castelein, René M.; Pasha, Saba
Abstract : Background: The development of proximal junctional kyphosis (PJK) after posterior spinal fusion in adolescent idiopathic scoliosis is a major problem. Changes in the global sagittal parameters as they relate to PJK have been reported after surgery, however, the relationships between the changes in the upper-instrumented vertebra (UIV) during and after surgery as they relate to development of PJK have not been quantified. We hypothesize that the compensatory changes in the unfused segments of the spine over time are correlated with the surgically induced changes in the UIV position. Methods: Sixty adolescent idiopathic scoliosis patients (with at least 1-year follow-up) who underwent posterior spinal surgery were included retrospectively. Global spinal parameters were calculated using 3-dimensional models of the spine, additional parameters [proximal junctional kyphosis angle (PJKA), cervical lordosis angle] were measured manually before surgery and at 3 postoperative follow-ups. The 3-dimensional position of the vertebral body centroids was calculated for T1, UIV, and lower-instrumented vertebra at all timepoints. The sagittal position of T1, UIV, and lower-instrumented vertebra were correlated to the cervical lordosis, PJKA, lumbar lordosis, and pelvic tilt. Results: The position of T1 and UIV were significantly more anterior at first erect for patients who developed PJK. The posterior shift of UIV at the most recent follow-up as compared with the preoperative position was significant in both the PJK and non-PJK cohort. A larger anterior shift in UIV at first erect correlated with a larger T1 and UIV posterior shift at the most recent follow-up. At the most recent follow-up, a more posterior position of the UIV correlated with a larger angle of PJKA ( P <0.05). Conclusion: Both a larger anterior shift of UIV between preoperative and first erect and a more posterior position of UIV at the most recent follow-up was correlated with a higher PJKA. A larger anterior shift in the position of the UIV after surgery was associated with a higher posterior shift of UIV at the last follow-up. The surgically induced changes in the UIV are an important parameter associated with the development of PJK. Level of Evidence: Level IV.